Analysis of a Neural Population Model for Interaction of LFP and Individual Action Potential. Issue 4 (29th January 2023) - Noyama, Hiroki; Yoshikai, Yuto; Bin, Li; Iguchi, Ryuki; Kotani, Kiyoshi; Jimbo, Yasuhiko
Abstract : The brain encodes various information through the interaction between macro‐scale phenomena such as Local Field Potential and micro‐scale phenomena such as individual neuron action potential time series. However, the interaction between micro‐ and macro‐scale phenomena that affects episodic memory remains unexplained. We propose a new mathematical framework to predict the parameter conditions under which theta phase precession occurs by constructing models that reproduce the micro‐ and macro‐scale phenomena separately and deriving their phase equations. It was found that phase locking or phase shift between the micro‐scale phase ϕ micro and the macro‐scale phase Φ Macro can reproduce different storage schemes. © 2023 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.